2016
DOI: 10.1002/eco.1716
|View full text |Cite
|
Sign up to set email alerts
|

Increased depth to the water table during river drying decreases the resilience of Gammarus pulex and alters ecosystem function

Abstract: River drying has drastic immediate effects on benthic invertebrates, but their high resilience reduces long-term effects on biodiversity and ecosystem functions (e.g. leaf litter decomposition). The hyporheic zone (saturated sediments below the riverbed) can be a refuge for invertebrates in dry rivers and a primary source of colonists supporting population resilience following flow resumption. However, factors such as the depth to the water table below the riverbed, which could determine the quality of the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 67 publications
5
31
0
Order By: Relevance
“…This suggests that survivorship of individuals within the mesocosms was reduced due to stranding above the free water and supports the findings of other studies (e.g. Navel et al, 2010;Vadher et al, 2015;Vander Vorste et al, 2016b). Vadher et al (2017) demonstrated the importance of sedimentology on the ability of G. pulex to move vertically through sediments.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This suggests that survivorship of individuals within the mesocosms was reduced due to stranding above the free water and supports the findings of other studies (e.g. Navel et al, 2010;Vadher et al, 2015;Vander Vorste et al, 2016b). Vadher et al (2017) demonstrated the importance of sedimentology on the ability of G. pulex to move vertically through sediments.…”
Section: Discussionsupporting
confidence: 89%
“…Previous research has reported reduced survivorship of common benthic invertebrates such as gammarids due to surface water loss in the surface (e.g. Poznańska et al, 2013) and subsurface (Vander Vorste et al, 2016b) sediments, and field investigations have reported reduced abundance of individuals with increasing intermittence (Clarke et al, 2010;Datry et al, 2014a) and duration of surface drying events (Storey, 2016). The majority of G. pulex individuals survived within the wet subsurface for periods of surface water loss \ 21 days, indicating that wet subsurface sediments can facilitate population persistence during short-term surface drying events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gammarus pulex is also important due to its role as both a predator and prey for fish and other invertebrate species (MacNeil et al, 1997;Kelly et al, 2002Kelly et al, , 2006. Gammarus pulex have been reported to migrate into subsurface sediments in response to biotic competition (McGrath et al, 2007), elevated temperatures (Wood et al, 2010) and water level reduction (Vander Vorste et al, 2016b;Vadher et al, 2017). Migration has been observed to depths of up to 2 m during adverse environmental conditions (Dole-Olivier et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In two karst rivers in the UK, Stubbington et al (2011) observed an increase in hyporheic abundance of Gammarus pulex and total invertebrate abundance during low-flow conditions, specifying that the hyporheic refuge use was more pronounced at sites where downwelling of surface water dominated (which may be interpreted as a major in bed sediments during a disturbance is not sufficient to demonstrate that the HZ is a true refuge (and not, for example, a graveyard), it is also necessary to measure the efficiency of subsequent recolonization from these HZ refuges (Kawanishi, Inoue, Dohi, Fujii, & Miyake, 2013;Vander Vorste, Malard, et al, 2016;Vander Vorste, Mermillod-Blondin, et al, 2016).…”
Section: Hyporheic Refuges and Nested Hyporheic Flowpaths (Predictimentioning
confidence: 99%